Bachelor Nursing Students’ Perception Towards Oncology Nursing Education and Their Future Intention in Chitwan, Nepal - Neupane, Laxmi; Upadhyay, Hari Prasad; Pokharel, Manju; Sharma, Sarojini (International Journal of Silkroad Institute of Research and Training, 2025)
Background: The rising cancer burden in low- and middle-income countries highlights the need for oncology nurses. Advancing oncology nursing education can reduce this burden, improve care, and foster student interest. The study aimed to assess nursing students’ perceptions of oncology nursing education at BPKMCH, Nepal. Method: A cross-sectional study was carried out among 137 BNS students at B.P. Koirala Memorial Cancer Hospital, Nursing College, Chitwan. Data were collected using a questionnaire. Ethical approval was obtained from the Institutional Review Committee (IRC), BPKMCH. The data collection was completed within two weeks. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 20 and interpreted through both descriptive and inferential statistics, including frequency, mean, standard deviation, and chi-square test. Result: The results showed that 51.1% of the respondents belonged to the 24-27 years age group, with a mean ± SD of 24.91 ± 2.975. The majority of the respondents were self-motivated to join the BNS program (86.1%). More than half of the respondents strongly agreed that the demand for oncology nursing is increasing (59.1%), and agreed that 66.4% were confident in assessing patients’ needs, followed by 62.0% were comfortable providing care, and 61.3% were confident in supporting patients and families. An equal number of respondents (83.9%) planned to pursue higher education in oncology nursing and work in oncology settings after graduation. The majority (73.0%) of the respondents had a positive perception of oncology nursing and the association was found between the level of perception and age (p-value=0.008), academic year (p-value=0.049), and family member in nursing (p-value =0.017). Conclusion: The study concludes that students had a positive perception of oncology nursing, recognizing its growing demand and planning higher education and careers in oncology. Nursing educators are recommended to further enhance these positive perceptions.